2015
DOI: 10.1177/0003489415574067
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in LOXHD1 Gene Cause Various Types and Severities of Hearing Loss

Abstract: Objective We present two families that were identified with novel mutations in LOXHD1, as a cause of non-progressive hearing loss. Methods One thousand three hundred fourteen (1,314) Japanese subjects with sensorineural hearing loss from unrelated families were enrolled in the study. Targeted genomic enrichment and massively parallel sequencing of all known non-syndromic hearing loss genes were performed to identify the genetic cause of hearing loss. Results Two patients in one family affected with homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…Severity varied from mild to profound and progression varied from stable to progressive HI in some frequencies. This phenotypic variability and audiogram configuration is in line with previous research on DFNB77 (Table ) …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Severity varied from mild to profound and progression varied from stable to progressive HI in some frequencies. This phenotypic variability and audiogram configuration is in line with previous research on DFNB77 (Table ) …”
Section: Discussionsupporting
confidence: 91%
“…It is not unlikely that the individuals with non‐congenital HI in fact have congenital HI, but that delayed diagnosis occurred due to lack of neonatal hearing screening or inconclusive test results. In literature, the reported onset of HI is mainly congenital, but varies from congenital to 8 years old (Table ) . One individual, described by Eppsteiner et al, had progressive HI that started at the age of 40 years .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their diagnoses included 20 genes and they estimated a diagnostic rate of 40% if they had not preselected their patient population [25]. They also provided an in-depth phenotypic analysis that adds to our knowledge of the clinical presentation associated with several genes, including LRTOMT, P2RX2, POU3F4, PTPRQ , and USH2A [2630]. …”
Section: Diagnostic Ratementioning
confidence: 99%
“…A series of studies have shown that patients with LOXHD1 mutations show progressive hearing loss, leading to profound‐to‐severe non‐syndromic hearing loss (Mori et al, ; Maekawa et al, ). By examining a large cohort of hearing loss patients (n = 8,074), we have recently reported 28 patients with LOXHD1 mutations and clarified the clinical features (Maekawa et al, ).…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 99%